Consolidation of clayey gouge amid permeating rock masses. Issue 3 (June 2015) - Trivedi, Ashutosh; Banik, Tanmay; Sukumar, Tanay; Kumar, Naresh; Jain, Akshay; Kumar, Amit
Abstract : There are numerous occurrences of soil–rock–water interaction in the natural geo-environment involving saturated clayey gouge consolidating amid permeating rock masses and draining laterally through a network of joints. In this paper, the concept of two-dimensional drainage for consolidation along the vertical direction for saturated clay has been applied to a layer of gouge amid rock joints. Solutions for pore water pressure distribution and average degree of consolidation have been computed. The orthogonal directions along which the drainage has been assumed for the derivation of these expressions are vertical direction (as in Terzaghi's theory of one-dimensional consolidation) and lateral direction. Initially, such a case corresponds to a Dirichlet problem applied to a rectangular gouge lamina. The deformations appearing in the vertical direction are a result of the effects of drainage in the lateral and vertical directions together. An expression for the relationship of time factor with the average degree of consolidation as a function of dimensionless parameter relating rock mass characteristics has been proposed.